Developing student worksheet based on iMindMap in animalia topic to train creative thinking ability - Angkin Ikalindhari; Reni Ambarwati; Dwi Anggorowati Rahayu (University of Muhammadiyah Malang, 2020)
Creative thinking ability can be trained to students during learning process using suitable learning materials. The purpose of this study was to produce a valid and practical student worksheet based on iMindmap in Animalia topic to train students’ creative thinking ability. This R & D referred to 4D model (define, design, develop, and disseminate) without disseminate phase. The validity of student worksheets was determined based on experts (material, education and media) assessment. Meanwhile, the practicality was evaluated based on teachers’ and students’ responses; and the readability of the worksheet decided based on Fry Graph. The data gained were analyzed descriptive-quantitatively. The research results revealed that the worksheet developed was declared as very valid (mode value: 4) and very practical based on practitioners' responses (mode value: 4) and students’ responses (the positive responses reached 90.45%). In addition, the readability test result was at level 10, which means that the worksheet was suitable for Grade 10. Hence, it can be concluded that the student worksheet based on iMindMap in Animalia topic can be used to train students’ creative thinking ability.